2019
DOI: 10.1111/head.13510
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene‐Related Peptide Modulators – The History and Renaissance of a New Migraine Drug Class

Abstract: Several lines of evidence pointed to an important role for CGRP in migraine. These included the anatomic colocalization of CGRP and its receptor in sensory fibers innervating pain‐producing meningeal blood vessels, its release by trigeminal stimulation, the observation of elevated CGRP in the cranial circulation during migraine with normalization concomitant with headache relief by sumatriptan, and translational studies with intravenous (IV) CGRP that evoked migraine only in migraineurs. The development of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 154 publications
(266 reference statements)
2
130
0
2
Order By: Relevance
“…Inhibition of the CGRP receptor has emerged as a promising target for the acute and preventive treatment of migraine (Edvinsson, 2018). Previously investigated small-molecule CGRP antagonists have demonstrated efficacy in the treatment of migraine; however, clinical studies involving telcagepant and MK-3207 revealed potential concerns regarding drug-induced elevation of liver enzymes, and clinical development of these compounds was discontinued (Hewitt et al, 2011;Ho et al, 2014;Hargreaves and Olesen, 2019). Although the exact mechanism of this hepatotoxicity is unknown, it was hypothesized to be partly attributable to the formation of reactive metabolites and not specific to CGRP receptor antagonism (Hargreaves and Olesen, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of the CGRP receptor has emerged as a promising target for the acute and preventive treatment of migraine (Edvinsson, 2018). Previously investigated small-molecule CGRP antagonists have demonstrated efficacy in the treatment of migraine; however, clinical studies involving telcagepant and MK-3207 revealed potential concerns regarding drug-induced elevation of liver enzymes, and clinical development of these compounds was discontinued (Hewitt et al, 2011;Ho et al, 2014;Hargreaves and Olesen, 2019). Although the exact mechanism of this hepatotoxicity is unknown, it was hypothesized to be partly attributable to the formation of reactive metabolites and not specific to CGRP receptor antagonism (Hargreaves and Olesen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previously investigated small-molecule CGRP antagonists have demonstrated efficacy in the treatment of migraine; however, clinical studies involving telcagepant and MK-3207 revealed potential concerns regarding drug-induced elevation of liver enzymes, and clinical development of these compounds was discontinued (Hewitt et al, 2011;Ho et al, 2014;Hargreaves and Olesen, 2019). Although the exact mechanism of this hepatotoxicity is unknown, it was hypothesized to be partly attributable to the formation of reactive metabolites and not specific to CGRP receptor antagonism (Hargreaves and Olesen, 2019). The absence of any ubrogepant-associated hepatotoxicity has been supported by safety data from recent clinical studies (Goadsby et al, 2019;Hutchinson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering acute treatments, the various TTTs are characterized by a striking comparable proportion of responders in terms of pain response at 2 hours, the most common efficacy indicator for abortive migraine treatments: 59% with triptans at standard doses (range 42.4% with oral frovatriptan-75.7% with subcutaneous sumatriptan), 59% with lasmiditan (100 and 200 mg), 61.4% with telcagepant (280/300 mg), 56.2% with BI 44370 TA (400 mg), and 60.8% with MK-3207 (100-200 mg). 17 As acutely observed by Olesen, "classification of migraine into different endophenotypes could aid diagnosis and treatment, but requires detailed characterization of different phenotypes." 11 By pooling together all the aforementioned findings it emerges that TTTs are effective in approximately 60% of migraineurs regardless of the type treatment (acute o preventative) or the drug mechanism (block of the trigeminal sensory system or antagonism of its principal neuropeptide).…”
mentioning
confidence: 99%
“…[14][15][16] This hypothesis has been recently taken into account also by Hargreaves and Olesen who raised the possibility that super-responders to CGRP mAbs might be those patients with autonomic signs in cranial tissues supplied by trigeminal innervation. 17 As acutely observed by Olesen, "classification of migraine into different endophenotypes could aid diagnosis and treatment, but requires detailed characterization of different phenotypes." 18 A very simple stepping stone in identifying TTTs responders could be the identification of migraineurs with unilateral pain.…”
mentioning
confidence: 99%